Kvinnorum i fadershus — kvinnliga prästers könsskapande - Meurling, Birgitta (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1999)
The aim with the article is to discuss how Swedish women clergy constitute gender in their professional career navigating between appreciation and resistance. It is obvious that the women clergy often are given a warm reception by people in the parish, but not always by their male colleagues. Here we speak of a kind of male homosociality which excludes women from the "top positions" in the Church of Sweden. In their professional position gender is always commented upon (a matter of fact that could be interpreted in a positive as well as a negative way): they are women clergy, not just clergymen. In the article the strategies developed by the women clergy are discussed, how the informants cope with their situation as women and clergy and their eventual potential to develop a new professional clerical role.